Nieregularny rozwój fonetyczny spowodowany frekwencją zachodzi w tekstach w ponad 60% wyrazów - Mańczak, Witold (Slavia Occidentalis, 2012)
The present writer believes that the form of words in all languages depends on three main factors, i.e., not only on regular sound change and analogical development, but also on what he calls irregular sound change due to frequency. The author analyses a fragment of a poem by Mickiewicz and indicates different reduced forms included in the section under examination, e. g. Polish waść < wasza miłość, mości < miłościwy, mego < mojego, dość < dosyć, ‑eś < OPol. jeś, ‑ą < *‑ętь, ‑emu < *‑u‑jemu, ‑y < *‑ъ‑jь, etc. These irregular reductions, which are very numerous, occur in texts in more than 60% of words. There are six arguments which prove that there exists a connection between irregular phonetic reductions and the frequency of use. Finally, the present writer quotes the opinion of a statistician according to which there is less than a chance in 10 million that this connection does not exist.